Worker self-selection and the profits from cooperation - Michael Kosfeld; Ferdinand von Siemens (Institute for the Study of Labor (IZA), 2008)
We investigate a competitive labor market with team production. Workers differ in their motivation to exert team effort and types are private information. We show that there can exist a separating equilibrium in which workers self-select into different firms and firms employing cooperative workers make strictly positive profits. Profit differences across firms persist because cooperation strictly increases output and worker separation requires firms employing cooperative workers to pay out weakly lower wages.
urn:nbn:de:101:1-20081217231
Keywords: D82; 330; Team work; self-selection; Gruppenarbeit; Arbeitsmarkttheorie; Asymmetrische Information; Arbeitsuche; Arbeitsnachfrage; Wettbewerb; Gewinn; Theorie